Shiga Toxin–Producing Escherichia coli Transmission via Fecal Microbiota Transplant. (29th September 2020) - Zellmer, Caroline; Sater, Mohamad R A; Huntley, Miriam H; Osman, Majdi; Olesen, Scott W; Ramakrishna, Bharat
Abstract: Fecal microbiota transplantation (FMT) is recommended therapy for multiply recurrent Clostridioides difficile infection. We report adverse events in 7 patients who received FMT from a stool donor who was colonized with Shiga toxin–producing Escherichia coli (STEC). No patients died of FMT-transmitted STEC. Improved screening can likely avoid future transmission.